2016
DOI: 10.1017/s1365100516000250
|View full text |Cite
|
Sign up to set email alerts
|

Does Inflation Targeting Matter? An Experimental Investigation

Abstract: We use laboratory experiments with human subjects to test the relevance of different inflation-targeting regimes. In particular and within the standard New Keynesian model, we evaluate to what extent communication of the inflation target is relevant to the success of inflation targeting. We find that if the central bank cares only about inflation stabilization, announcing the inflation target does not make a difference in terms of macroeconomic performance compared with a standard active monetary policy. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(4 citation statements)
references
References 52 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…In particular, a number of LtFEs have been conducted within NK models, albeit in their simple linearized form, to investigate inflation persistence (Adam 2007), the appropriate design of Taylor rules (Assenza et al 2018;Pfajfar and Zakelj 2016), disinflationary policies (Cornand and M'baye 2016), and the importance of the expectation channel for macroeconomic stabilization (Kryvtsov and Petersen 2013;Pfajfar and Zakelj 2014); see also Assenza et al (2014) for a survey of LtFEs in macroeconomics. In particular, a number of LtFEs have been conducted within NK models, albeit in their simple linearized form, to investigate inflation persistence (Adam 2007), the appropriate design of Taylor rules (Assenza et al 2018;Pfajfar and Zakelj 2016), disinflationary policies (Cornand and M'baye 2016), and the importance of the expectation channel for macroeconomic stabilization (Kryvtsov and Petersen 2013;Pfajfar and Zakelj 2014); see also Assenza et al (2014) for a survey of LtFEs in macroeconomics.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a number of LtFEs have been conducted within NK models, albeit in their simple linearized form, to investigate inflation persistence (Adam 2007), the appropriate design of Taylor rules (Assenza et al 2018;Pfajfar and Zakelj 2016), disinflationary policies (Cornand and M'baye 2016), and the importance of the expectation channel for macroeconomic stabilization (Kryvtsov and Petersen 2013;Pfajfar and Zakelj 2014); see also Assenza et al (2014) for a survey of LtFEs in macroeconomics. In particular, a number of LtFEs have been conducted within NK models, albeit in their simple linearized form, to investigate inflation persistence (Adam 2007), the appropriate design of Taylor rules (Assenza et al 2018;Pfajfar and Zakelj 2016), disinflationary policies (Cornand and M'baye 2016), and the importance of the expectation channel for macroeconomic stabilization (Kryvtsov and Petersen 2013;Pfajfar and Zakelj 2014); see also Assenza et al (2014) for a survey of LtFEs in macroeconomics.…”
Section: Introductionmentioning
confidence: 99%
“…They find that increasing the interest rate in response to stock price bubbles has only a limited effect in 6. Most experiments with monetary policy use a New Keynesian framework and do not include asset markets, such as Arifovic and Petersen (2017), Assenza et al (2021), Cornand and M'baye (2018), Hommes, Massaro, and Salle (2019), Hommes, Massaro, and Weber (2019), Kryvtsov and Petersen (2021), Petersen (2015), Pfajfar and Žakelj (2018), Noussair, Pfajfar, and Zsiros (2021). reducing bubbles.…”
Section: Related Theoretical and Experimental Literaturementioning
confidence: 99%
“…Their findings revealed that the framework practicality reduced exchange rate pass-through in Thailand and South Korean, while indifferent for the Philippines and Indonesia. Furthermore, many other studies also showed that inflation targeting framework is most effective in financial and banking sector stability (Fazio et al, 2015;Tabak et al, 2016;Ismailov et al, 2016;Soe and Kakinaka, 2018;Cornand and M'Baye, 2018). Nevertheless, some studies reported on the efficacy of the inflation targeting framework in exchange rate policy as in Khodeir (2012), who explored the flexible targeting regime…”
Section: Review Of the Literaturementioning
confidence: 99%